Sistematización de la experiencia de diseño y mejoramiento de perfiles de cargo y procesos de inducción de personal de la empresa consultora de ingeniería de diseño de proyectos - Alfaro Ordoñez, Pamela Milagros (2017)
The intervention project, when receiving an adequate induction process, allows correcting organizational and administrative aspects of the human resources management, creating a sense of belonging in employees, because most of the staff is not familiar with the Organizational culture of the company. This was born from the need to improve and optimize the human resources processes, thus generating efficiency and effectiveness, in addition to increasing productivity, which in the future will help to ensure that the hiring process is carried out in an organized way and have an induction process within the Company that allows employees to know the Organizational Culture in a suitable way. By improving the format of the occupational profiles, it will allow to know in a specific way the functions of each position, besides with the induction manual, a correct process of induction for both former and new employees can be developed.